1995
DOI: 10.1007/bf00238548
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exposure to oxygen at 101 and 150 kPa on the cerebral circulation and oxygen supply in conscious rats

Abstract: Hyperbaric oxygen at pressures of 300 to 500 kPa has been shown to induce changed distribution of cerebral blood flow (QCBF) in rats, in places reducing the supply of the supplementary O2. Thus, in the present study, the effect of hyperoxia at 101 (group 1, n = 9) and 150 (group 2, n = 9) kPa O2 on cerebral blood flow distribution and central haemodynamics was tested in conscious, habituated rats. During the control period the systolic arterial pressure (BPs), heart rate (fc), breathing frequency (fb), cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 12 publications
2
12
1
2
Order By: Relevance
“…Experimental and human studies demonstrated that hyperoxia may slightly reduce CBF, especially under hyperbaric conditions. 36,37 However, PaO 2 values observed during hyperbaric oxygenation are markedly higher than those in the present investigation (PaO 2 Ϸ200 mm Hg). James et al 38 observed that increasing PaO 2 above the normal range (up to 450 mm Hg) does not significantly influence gray and white matter blood flow.…”
Section: Study Limitationscontrasting
confidence: 55%
“…Experimental and human studies demonstrated that hyperoxia may slightly reduce CBF, especially under hyperbaric conditions. 36,37 However, PaO 2 values observed during hyperbaric oxygenation are markedly higher than those in the present investigation (PaO 2 Ϸ200 mm Hg). James et al 38 observed that increasing PaO 2 above the normal range (up to 450 mm Hg) does not significantly influence gray and white matter blood flow.…”
Section: Study Limitationscontrasting
confidence: 55%
“…Total CBF is decreased between 20 and 30%, while the oxygen supply is still maintained [10][11][12]. However, experimental data show that changes of CBF caused by HBO are dependent on the region, and also areas of increased CBF were found [13].…”
Section: Discussionmentioning
confidence: 72%
“…The present data demonstrate that normal lung function and respiratory regulation were preserved during this O 2 pressure, which is a common treatment pressure for humans. The respiratory balance has also been reported to be normal in normoxic hyperbaric exposures of up to 4.1 MPa (Furset et al 1989;Risberg et al 1990;Bergù and Tyssebotn 1995b). Conversely, hyperventilation occurred during O 2 exposures to pressure that exceeds those used for clinical treatment; 350 kPa O 2 in man (Lambertsen 1978) and 500 kPa O 2 in rats (Bergù et al 1988;Bergù and Tyssebotn 1992a).…”
Section: Kpa Ambient Pressurementioning
confidence: 85%
“…The unchanged EDP and SV eliminate FrankStarting mechanisms as an explanation for the increase in LVP and cardiac contractility. Thus, the augmented hemodynamic parameters may be due to the combined eects of the ambient pressure increase per se (Ask and Tyssebotn 1988;Stuhr et al 1989), an increase in breathing gas density (Bergù and Tyssebotn 1992c;Risberg et al 1995), and the O 2 pressure increase (Bergù and Tyssebotn 1995b;Risberg et al 1995). Of these factors, the increase in O 2 pressure has been shown to be most potent since a pressure increase of only 10 kPa O 2 reduces f c and increases cardiac contractility (Risberg et al 1995), whereas normoxic ambient pressures up to 7 MPa (Aanderud et al 1985;Stuhr et al 1989) did not in¯uence the f c , but increased contractility (Ask and Tyssebotn 1988;Stuhr et al 1989).…”
Section: Kpa Ambient Pressurementioning
confidence: 96%